Surgical implications and variability in the use of the flat epithelial atypia diagnosis on breast biopsy specimens. (August 2017) - Samples, Laura S.; Rendi, Mara H.; Frederick, Paul D.; Allison, Kimberly H.; Nelson, Heidi D.; Morgan, Thomas R.; Weaver, Donald L.; Elmore, Joann G.
Abstract: Objectives: Flat epithelial atypia (FEA) is a relatively new diagnostic term with uncertain clinical significance for surgical management. Any implied risk of invasive breast cancer associated with FEA is contingent upon diagnostic reproducibility, yet little is known regarding its use. Materials and methods: Pathologists in the Breast Pathology Study interpreted one of four 60-case test sets, one slide per case, constructed from 240 breast biopsy specimens. An electronic data form with standardized diagnostic categories was used; participants were instructed to indicate all diagnoses present. We assessed participants' use of FEA as a diagnostic term within: 1) each test set; 2) 72 cases classified by reference as benign without FEA; and 3) six cases classified by reference as FEA. 115 pathologists participated, providing 6900 total independent assessments. Results: Notation of FEA ranged from 0% to 35% of the cases interpreted, with most pathologists noting FEA on 4 or more test cases. At least one participant noted FEA in 34 of the 72 benign non-FEA cases. For the 6 reference FEA cases, participant agreement with the case reference FEA diagnosis ranged from 17% to 52%; diagnoses noted by participating pathologists for these FEA cases included columnar cell hyperplasia, usual ductal hyperplasia, atypical lobular hyperplasia, and atypical ductal hyperplasia. Conclusions: We observed wide variation in the diagnosis of FEA among U.S. pathologists. This suggests that perceptions of diagnostic criteria and any implied risk associated with FEA may also vary. Surgical excision following a core biopsy diagnosis of FEA should be reconsidered and studied further. Highlights: We observed wide variation in the diagnosis of FEA among U.S. pathologists. Perceptions of diagnostic criteria and any implied risk for FEA may also vary. FEA, CCH, UDH, and ALH should be compared in greater detail during case review. Surgical excision following core biopsy diagnosis of FEA may not be necessary. Educational interventions may refine understanding, reduce diagnostic variation.